Exploration of the impact of inflammatory bowel disease fatigue on the health-related quality of life of adults - Radford, Shellie Jean (2020)
Background: Fatigue is a frequently reported symptom of Inflammatory Bowel Disease (IBD), experienced by patients with active disease and when in remission. Fatigue related to chronic conditions plays a significant negative role in health-related quality of life (HRQoL), but patients’ experience of this have not been researched in IBD.